2012
DOI: 10.1159/000345205
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Embryopathy: A Developmental Perspective from Fertilization to Adulthood

Abstract: Maternal diabetes mellitus is one of the strongest human teratogens. Despite recent advances in the fields of clinical embryology, experimental teratology and preventive medicine, diabetes-related perturbations of the maternofetal unit maintain a considerable impact on the Healthcare System. Classic consequences of prenatal exposure to hyperglycemia encompass (early) spontaneous abortions, perinatal death and malformations. The spectrum of related malformations comprises some recurrent blastogenic monotopic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 178 publications
0
32
0
4
Order By: Relevance
“…7, 5456 Although VACTERL association is usually sporadic, a relatively small number of familial cases have been described, and there may be an over-representation of VACTERL-type anomalies in relatives of probands. 57, 58 A thorough family history can help with the differential diagnosis (e.g., the possibility of other conditions may be raised) and can help inform discussions regarding recurrence risks.…”
Section: Suggested Diagnostic Approachmentioning
confidence: 99%
“…7, 5456 Although VACTERL association is usually sporadic, a relatively small number of familial cases have been described, and there may be an over-representation of VACTERL-type anomalies in relatives of probands. 57, 58 A thorough family history can help with the differential diagnosis (e.g., the possibility of other conditions may be raised) and can help inform discussions regarding recurrence risks.…”
Section: Suggested Diagnostic Approachmentioning
confidence: 99%
“…Of note, we also found that the somites of high-glucose embryos are smaller along the anteroposterior axis compared with those in control embryos. The smaller somites observed in high-glucose embryos might possibly be related to the observation that the risk for costovertebral defects and VACTERL (vertebral defects, anal atresia, cardiac defects, tracheo-esophageal fistula, renal anomalies, and limb abnormalities) is increased in human diabetic embryopathy (52). Somitogenesis is regulated by oscillation of Notch signaling in presomitic mesoderm (49).…”
Section: Discussionmentioning
confidence: 99%
“…FFS has a strong association with maternal diabetes, and maternal hyperglycaemia is one of the strongest human teratogens 7. Most of the congenital malformations occurring in infants of diabetic mothers are blastogenic in origin,4 which can result in a significantly higher risk for congenital malformations including neural tube defects, caudal dysgenesis, congenital heart defects, renal anomalies and femoral hypoplasia.…”
Section: Discussionmentioning
confidence: 99%